THE EFFECT OF HYPNOTHERAPY ON PRIMARY DISMENORE IN ADOLESCENTS - Hemi Fitriani; Achmad A (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
The health problem that often threatens of young women in the puberty period is dysmenorrhea. The survey revealed that 54.89% of adolescents ages 14-19 years in Indonesia experience dysmenorrhea in 2011. Dysmenorrhea would be impacted in adolescents’ daily activities including g unable to take part in activities at school, lacking concentration and finally disrupting adolescent achievement. Dysmenorrhea requires proper and effective treatment so that adolescents will maintain and improve their health. This study aimed to determine the effect of hypnotherapy on the primary adolescent dysmenorrhea. The research that was a Quasi-Experiment study, with the design of the Non-equivalent Control Group. The research sample consisted of 13 students taken by purposive sampling. The Numeric Rating Scale (NRS) used for data collection. The univariate analysis applied to analyze the median, and bivariate analysis used the Mann Whitney test. Statistically, the study obtained pValue = 0.018, there was a significant effect of hypnotherapy on decreasing primary dysmenorrhea. Health workers may use hypnotherapy as an alternative intervention to overcome primary dysmenorrhea in adolescents.Keywords: Adolescence, hypnotherapy, primary dysmenorrhea.